Symmetrical Communication in Public Relations: Dynamics, Challenges, and Opportunities, A Systematic Literature Review - Naomi Shava Try Augusta; Dewa Ayu Geandini Adithi Kirana; Dwi Aprilia Zerlinda (UMSU, 2026)
This study aims to synthesize the dynamics, challenges, and opportunities for implementing symmetrical communication in public relations practice through a systematic literature review of scientific articles from 2021–2025. The study results indicate that symmetrical communication has developed as a strategic approach that emphasizes two-way dialogue, openness, and active participation between organizations and the public, especially in the digital context. Its implementation is dynamic and contextual, influenced by leadership factors, organizational culture, and the use of technologies such as social media and artificial intelligence. However, its implementation still faces various challenges, such as the dominance of organizational control, limited transparency, and low levels of meaningful participation. On the other hand, symmetrical communication offers strategic opportunities to increase trust, engagement, relationship quality, and organizational reputation. Thus, symmetrical communication is a relevant, adaptive approach in the digital era, but requires organizational commitment to consistently implement dialogic and participatory values.